Incarnation : the person and life of Christ - Torrance, Thomas F. (Thomas Forsyth), 1913-2007.; Walker, Robert T. (Downers Grove, Ill. : IVP Academic ; Milton Keynes ; Colorado Springs : Paternoster, 2008)
"The late Thomas F. Torrance has been called "the greatest Reformed theologian since Karl Barth" and "the greatest British theologian of the twentieth century" by prominent voices in the church and academy." "His new book on Christology addresses both heart and head through a deeply biblical, unified, Christ-centered and trinitarian theology. Torrance presents a full account of the meaning and significance of the life and person of Jesus Christ, demonstrating that his work of revelation and reconciliation can only be understood in the light of who he is - real God and real man united in one person. Torrance contends that the whole life of Jesus Christ-from his birth, through his ministry, cross, resurrection and ascension to his second coming - is of saving significance."--BOOK JACKET.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Person and offices; Incarnation